The Enhancement Of Production Capacity And Quality Of Organic Fertilizer Through Implementation Of Grinding And Sieving Machines. - Irnia Nurika (Journal of Innovation and Applied Technology, 2019)
The regularly increasing price and scarcity of inorganic fertilizer resulted a serious problem faced by the vegetable farmer in Pujon-Malang. Alternatifely the use of organic fertilizer as a subtitute for inorganic fertilizer is become an option for resolving the issue. The small and medium size enterprises (SMEs) Barokah Jaya and Mandiri are the SMEs producing organic fertilizer which utilzed local organic materials. However, in the its production process these two SMEs have constrains such as the unhomogenise of size of the organic fertilizer which directly affected to value of general quality of the fertiliser product. Therefore this project aims to implement the grinding and sieving machines on the process which are able to enhance the product quality. Through the implementation of these two machines, resulted (i) the increasing of production capacity 70-100% which is followed by the enhancement of value added product and market networks, (ii) resulted standarized organic fertilizer, (iii) the application of composting technology which used those two machines has been socialised.